2021
DOI: 10.1530/eje-21-0330
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of repeat fineneedle aspiration biopsy for AUS/FLUS thyroid nodules

Abstract: Objective: To determine the proportion of aspirates reclassified into each Bethesda category; and to assess the rates of malignancy in each of them on repeat fine needle aspiration biopsy (RFNA) following an AUS/FLUS diagnosis. Design: Systematic review and meta-analysis Methods: On February 2019, Pubmed/MEDLINE, EMBASE, WoS and the Cochrane Library were searched for articles published from January 1, 2007. All studies published in English describing RFNA outcomes in AUS/FLUS nodules were included. PRISMA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
12
1
Order By: Relevance
“…The rate of repeat indeterminant cytology in this study was slightly higher than what was reported in a recent meta-analysis of repeat cytology. 8 Potential sources of this discrepancy could be differences in patient populations (data taken from a major referral center) or differences in the availability and use of ancillary molecular testing at these other institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of repeat indeterminant cytology in this study was slightly higher than what was reported in a recent meta-analysis of repeat cytology. 8 Potential sources of this discrepancy could be differences in patient populations (data taken from a major referral center) or differences in the availability and use of ancillary molecular testing at these other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…One option for managing an indeterminant nodule is to perform a repeat biopsy (rebiopsy), which reportedly renders a more definitive diagnosis for between 55% and 76% of initially indeterminant nodules. [6][7][8][9] A more recently developed approach is to use ancillary molecular testing to risk-stratify these cytologically indeterminant lesions. The latest version of 1 such test (ThyroSeq version 3 [v3]) assesses 112 genes using nextgeneration sequencing technology to identify point mutations, gene fusions, copy number alterations, and gene expression alterations associated with neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent meta-analysis showed that repeating a fine needle-aspiration biopsy in atypia/follicular lesions of undetermined significance reclassifies 50% of them as benign with a negative predictive value greater than 96%; and reclassifies another 15% of the nodules into higher suspicion categories. 69 These results are at least as good as those achieved by current molecular tests. 47 Therefore, it remains unclear what is the incremental benefit of molecular tests in this category; and whether it is cost-effective.…”
Section: Institutional Diagnostic Threshold For Malignancy In Ras-lik...mentioning
confidence: 63%
“…Therefore, longer follow‐up data in nodules with benign/negative molecular tests' results is necessary to validate their real‐world negative predictive value. Furthermore, a recent meta‐analysis showed that repeating a fine needle‐aspiration biopsy in atypia/follicular lesions of undetermined significance reclassifies 50% of them as benign with a negative predictive value greater than 96%; and reclassifies another 15% of the nodules into higher suspicion categories 69 . These results are at least as good as those achieved by current molecular tests 47 .…”
Section: Molecular Tests For the Evaluation Of Cytologically Indeterm...mentioning
confidence: 99%
“…The limitations and diagnostic difficulties of FNAB may cause false-negative and falsepositive results. Even if the initial cytological results are benign, it has been reported that the risk of malignancy is as high in TN with suspicious USG (12,13).…”
Section: Introductionmentioning
confidence: 99%